Model Kajian Pesantren: Studi Kritis terhadap Buku Dinamika Sistem Pendidikan Pesantren karya Mastuhu - Fauzi Fauzi (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2015)
As typical Indonesian education institute, pesantren with all its component, tradition, culture, and uniqueness have drawn attention many expert and researchers. Pesantren existence has given great contribution to enhancement of the quality of human life. Many role have been played by pesantren; in social, political, economics, cultural aspect; and of course religious aspect which its basic study. These realities in turn have invited the attention of many circles to continuously examine, checking, or studying dynamics, growth, and also existence of pesantren. Among the study result is Mastuhu’s research: Dynamics of System of Education Pesantren, a Study about Element and Value of Pesantren Educational System. With this masterpiece, Mastuhu trying to promote the form of study pesantren which do not merely touching manifest (visible) aspect, but trying to find the values which is consisted inside that manifest; so can found positive, negative, and plus-minus items from pesantren’s education which need and needn’t to be developed in national’s education system. Through this article, the writer will express the work content from a perspective of its study approach.